Implementasi Kebijakan Pemerintah dalam Pembinaan Penataan Pasar Karombasan Kecamatan Wanea Kota Manado - Jacobis, Edwin; Singal, Alfi Martone; Rumengan, Hendry; Robial, Frangky Erwin Dede; Giroth, Lady Grace Jane; Pangalo, Fernando Alex (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to describe and analyze the implementation of government policies in the management and development of the Karombasan Market, Wanea District, Manado City. The method used in this research is a qualitative approach research method. The aim of descriptive research is to create systematic, actual and accurate descriptions, images or paintings regarding the facts, as well as the properties and relationships between the phenomena being investigated. The results of the research show that the government has carried out their respective duties but it is still not going well, even though they hold a large responsibility in the management and development of the Karombasan Market in Manado, they cannot do much even though they have already held socialization because of the Traders do not follow the rules that have been made and mutually agreed upon but it doesn't have much of an impact because not many traders participate and the government has carried out socialization for a long time and is no longer held. And also because traders are used to situations like that because from the start of their sales they were not grouped according to the types of sales. The arrangement and development of the Manado Karombasan Market did not run optimally because since the planning, traders were not placed in accordance with the applicable rules or regulations. The government is less firm in following up on the problems faced, such as traders' stalls which are not well organized and do not comply with the rules, traders do not participate enough in the arrangement and cleanliness of Manado's Karombasan Market. The absence of regional regulations governing traditional markets, especially in the city of Manado, makes it difficult for the government to take reference from where to act and manage these markets.